Kendali Alat Sterilisasi Sepatu Berbasis Mobile - Rakhmad Dhani; Arsan Kumala Jaya; Ahmad Rofiq Hakim (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Shoes frequently come into contact with floors and the outdoor environment, making them a potential medium for spreading bacteria and viruses. This study aims to design and build an IoT-based shoe sterilization system that can be monitored and controlled via an Android application. The system uses an ESP32 microcontroller, DHT22 temperature and humidity sensor, MC-38 door sensor, and LJ12A3-4-Z/BX proximity sensor. The sterilization process uses a 254 nm UV-C lamp integrated with Firebase Realtime Database. The system can automatically detect shoe types, set a maximum temperature of 34°C for sneakers and 50°C for safety shoes, and automatically turn off the UV-C lamp when the door is opened. Test results show all components worked as designed. The integration of ESP32, Firebase, and the Android app proved to be an effective IoT-based sterilization solution.